Vitamin D insufficiency is high in Malaysia: A systematic review and meta-analysis of studies on vitamin D status in Malaysia - Mohd Saffian, Shamin; Jamil, Nor Aini; Mohd Tahir, Nor Asyikin; Hatah, Ernieda (Frontiers in Nutrition, 2022)
Purpose To estimate the vitamin D status of participants residing in Malaysia. Methods PubMed, Scopus, Web of Science, and MyJurnal were searched up to June 2022 without language restrictions. Studies that reported the 25-hydroxyvitamin D [25(OH)D] concentrations and defined their cut-off for deficiency or insufficiency from healthy participants residing in Malaysia were included. The random effects model was used to pool vitamin D status using established cut-offs of <30, <50, and <75 nmol/L according to age group. Results From 299 studies screened, 32 studies were included in the meta-analysis. The pooled proportion for <30 nmol/L was 21% (95% CI 9–36, n = 2,438 from 10 studies), while the pooled proportion <50 nmol/L was 64% (95% CI 56–72, n = 13,977 from 30 studies), and <75 nmol/L was 85% (95% CI 61–100, n = 1,376 from five studies). Heterogeneity was high (I2 ranged from 98–99%). Higher proportions of vitamin D insufficiency (defined as <50 nmol/L) were found in participants living in the urban areas (compared to rural areas), in females (compared to males), and in Malays and Malaysian Indians (compared to Malaysian Chinese) ethnicities. Conclusion More than half of Malaysians have insufficient vitamin D levels, despite being a country that is close to the equator. We strongly urge prompt public health measures to improve the vitamin D status in Malaysia. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42021260259].